Study on Community Participation in The Land Clearing without Burning in Gambut Sub-District, South Kalimantan - Fonny Rianawati; Susila wati (Center for Journal Management and Publication, 2015)
In connection with the Environment Minister regulation number 10 year 2010 about the Mechanism of Pollution Prevention and Environment and Life Damage chapter II, Article 3 (1) said that all of business and activities that use the forest or land should implementÂ land clearing without burning (LCWB) and is expected that all participating land preparation activities to implement these policies. This study was conducted to determine the level of community perception on LCWB and the land waste utilization by the community in Gambut Sub-district, South Kalimantan, Indonesia. The results showed that 15 respondent (49.83%) already knew about land clearing without burning. Low level of community participation is caused by community understanding about CLBW still low. About 64 % of respondents was included in the good category because the community has an interest to cultivate a waste from land clearing to decrease environment contamination. Â About 60 % of the community thought that LCWB waste can be used for various purposes. Waste types which usually utilize by community was grass and rice husks.Â The wastes were used as organic fertilizer and animal feed without further processing.